Verification of IRT with the peltier technique - Variyart, Weerachai; chinchusak, wanchai (Bulletin of Applied Sciences, 2022)
Recently, the demand for infrared thermometers (IRT) is increasing continuously. They are widely used in many applications, such as measuring temperature at the screening points and public health facilities to prevent the spread of the COVID-19 virus. However, it is not reliable due to their limit of tolerance, which results in an increased risk of the epidemic of the COVID-19 virus.Verifying those IRTs with a black body can be costly and unnecessarily for high accuracy. Techniques for verifying the IRT with smart kits are detailed in the document of ASTM E1965-98 [1]. By using these techniques for the smart kit, the measuring range with the accuracy of ± 0.3°C can be cover up the temperature of 36°C to 39°C. These methods of verification also improve the efficiency and reliability of infrared thermometers.